Factors to consider when estimating congestion costs and evaluating potential congestion reduction strategies. - Litman, Todd (My University, 2013)
Traffic congestion can be measured in various ways that result in very different conclusions about the nature of the problem and optimal solutions. This article describes various factors that affect congestion cost estimates and the evaluation of potential congestion reduction strategies. It discusses how these factors influence planning decisions, and describes best practices for comprehensive evaluation of congestion impacts.
Keywords: Individualverkehr; Fahrradverkehr; Stadtverkehr; Verkehrsbelastung; Autoverkehr; Kostenanalyse; Verkehrskosten; Evaluation; Stau